Mining of genes encoding for DNA-manipulating enzymes from hot springs using metagenomic techniques - Mokoena, Morena India (Vaal University of Technology, 2019)
The use of conventional culture-based approach results in vast majority of microbes (90 - 99%) unaccounted for. However, over the past years, the use of metagenomics, which is a culture-independent comprehensive approach has enabled researchers to access nearly 100% of the microbiome. In this study, three hot springs (44 – 70 oC) in Limpopo province of South Africa were investigated as potential sources of genes encoding for DNA-manipulating enzymes (DNA polymerase, DNA ligase and endonuclease), which are central in genetic engineering. They are usually grouped into four broad classes (nucleases, ligases, polymerases and modifying enzymes) depending on the type of the reaction they catalyze. Accordingly, hot spring metagenomic DNA was successfully extracted using modified SDS-CTAB method involving gel purification and electroelution. Consequently, a portion of the extracted metagenomic DNA was used for sequencing and another for fosmid library construction. Sequencing was done using Illumina MiSeq next generation sequencing platform and sequence data analyzed and de novo-assembled using CLC Genomic Workbench, which resulted in 5 681 662 reads and 7 338 contigs. A metagenome expression fosmid library of approximately 2.16 x 103 clones was also constructed using CopyControl™ HTP Fosmid Library Production Kit with pCC2FOS™ Vector. A BLAST algorithm in NCBI revealed 57 distinct genes for DNA polymerase, 29 genes for DNA ligase and more than 100 genes for endonuclease II enzymes. Hence, three genes related to thermophiles representing genes for DNA polymerase, DNA ligase and endonuclease II were selected. Accordingly, the three genes were codon-optimized, synthesized and successfully cloned into pET- 30a (+) and overexpressed in Escherichia coli BL21 (DE3) by inducing with 0.5 mM IPTG and incubating overnight at 16ºC. The cells were lysed using B-PER Reagent, protein extracted and purified using AKTA start protein purification system and purity of 85- 95 % was achieved. From this study, it can be concluded that metagenomics as an approach, can be used to mine for putative DNA-manipulating enzymes from hot spring metagenome. Besides, further study should be conducted to formulate the developed DNA-manipulating enzymes and study the practical application and chart way for commercialization. Moreover, the constructed fosmid library could also be screened for potentially novel thermo-stable biomolecules of industrial and therapeutic importance.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Hot spring; Metagenomic library; DNA-manipulating enzymes; Sequencing; Cloning; Expression; Dissertations, Academic -- South Africa.; Metagenomics.; Biotechnology.; DNA -- Synthesis.; Enzymes.